Effectiveness of the "Let’s expose better" Program to Promote Oral Expression in students of a Peruvian University - Montoya, Darwin Augusto Moscoso; Carpio, Pablo Miguel Carrasco del; Espezú, Germán Christopher Figueroa; García, Josefina Mollo; Gamis, Raúl Demetrio Arredondo; Gutiérrez, María del Pilar Carreño (Migration Letters, 2023)
The purpose of this study is to verify the efficiency of the "Let’s expose better" program to improve oral expression in the University of Arequipa. The population was made up of students drawn from the first cycle of the professional schools of the Peruvian University that was the subject of study. For the selection, an incidental non-probabilistic procedure was used, considering the attending students and those who could be accessed at the time of applying the instrument. After applying the instrument, 240 students were obtained as a sample. The observation technique was used and an evaluation grid was used as an instrument to evaluate the observations, designed by Álvarez and Parra in Colombia (2015). The results obtained after applying the Wilcoxon statistic show a p-value lower than 0.05 that corroborates the difference between the pretest and posttest results, after applying the oral expression program. The effect size d is large, being 5.47089, also validating the difference between both tests, showing that it exists and is important. Regarding the statistical power, the value is 1.0000 and these results can be generalized to the entire population that received and carried out said program to improve their oral expression, as its effectiveness was demonstrated.